The Effect of Blended PBL Assisted with Advance Organizer and Thinking Style on Understanding and Application of Digital Electronics Concepts - Godlief Erwin Semuel Mige; Punaji Setyosari; Saida Ulfa; Henry Praherdiono (JTP - Jurnal Teknologi Pendidikan, 2023)
This study aims to see the effect of Blended Problem-Based Learning assisted with Advance Organizer (BPBL AO) model in the experimental class and Direct Learning in the control class, the moderator variable of Thinking Style (Internal and External), on the dependent variable Digital Electronics Concept Understanding and Digital Electronics Concept Application and the interaction effect of the independent variable and moderator variable on the dependent variable. This research is a quantitative research with a quasi-experimental approach with a 2x2 factorial design, Multivariate Analysis of Variance (MANOVA) is used to analyze research data. The results of the study are (1) there are differences in learning outcomes between students taught with BPBL AO and students taught with direct learning on Digital Electronics Concept Understanding and Digital Electronics Concept Application, (2) there are differences in higher order thinking skills between students who have internal thinking styles and external thinking styles in the Digital Electronics Concept Understanding dimension and while they tend to be the same or there is no difference in Digital Electronics Concept Application, and (3) between the learning strategies applied and the thinking styles possessed by students on the learning outcomes of Digital Electronics Concept Understanding and Digital Electronics Concept Application, there is no interaction effect.  The application of BPBL AO can improve critical thinking skills for problem solving without depending on their thinking style. This research shows that BPBL AO can stimulate students to think more critically, analyze information, link digital electronics concepts with the real world, and produce creative solutions in problem solving.